The child – Object or subject of child care? - Gabriel, Thomas (Children and youth services review, 2023)
•Contemporary questions of child and youth care are to be informed by historical knowledge.•Subject orientation is a fundamental prerequisite of educational processes.•Subjectification and objectification need to be theoretically framed in child welfare. The term “subject” and its theoretical implications are essential to German tradition of socialpedagogy and social work. If we look back in history, there is a sharp contrast to the practices of social work, especially in the field of child and youth welfare. This applies to Switzerland, Germany and internationally. In Swiss history, objectification is most clearly expressed in the German term “Verdingkinder”, which terminologically indicates the active process of objectification (Ding = object). Informed by historical research, questions can be addressed to current practice of child and youth welfare. Against the background of current research results, it seems too easy to dispose of the critical questions in the past. The article looks in the historical rear-view mirror to assess the Swiss “state as a parent” and to develop conclusions for contemporary questions of child and youth Welfare. The analytical framework will focus on the categories of objectification and subjectification, informed by Martha Nussbaums theories and theories of the German-speaking socialpedagogy by Michael Winkler.